Avaliação da força muscular respiratória em pacientes mastectomizadas - Ribeiro, Allex Junior Holanda (2022)
Introduction: Breast Cancer (CA) is configured as a disease of high incidence in the Brazilian female population. According to estimates, 66,280 new cases are calculated for the year 2022, which is also the main reason for cancer deaths in this population. The surgical procedure of mastectomy is the most suitable for breast cancer. Any thoracic surgical procedure reveals some level of respiratory dysfunction, which may infer respiratory muscle function. Objective: Evaluate respiratory muscle strength in patients undergoing mastectomy. Methods: This is an exploratory, descriptive, interventionist, cross-sectional, quantitative study. The study evaluated 21 patients with breast cancer, aged between 35 and 86 years, who underwent mastectomy (radical and simple) with and without axillary dissection, attended at the Education Group in Oncological Studies (GEEON). Participants underwent manovacuometry, which consists of a test to measure respiratory muscle function by measuring maximal inspiratory pressure (MaxIP) and maximal expiratory pressure (MaxEP), to observe changes in respiratory muscle function or weakness. of the breathing muscles (through the Lower Limit of Normality – LLN). These data were correlated with the variables: Age; alcoholism; smoking; surgery time; location of the tumor; type of breast surgery; breast reconstruction; radiotherapy; hormone therapy; chemotherapy. Results: The means found with their respective standard deviations were: MaxIP test (65.7 ± 47.8); expected MaxIP (68.4 ± 10); LLN MaxIP (25.2 ± 10); MaxEP test (61.1 ± 29.7); expected MaxEP (83.8 ± 21.1); LLN MaxEP (33.7 ± 16.3). As for the correlations, the following findings were found: to observe that the results associated with respiratory muscle weakness (inspiratory and expiratory) related to variables related to lifestyle and clinical characteristics, did not contemplate an important level of statistical significance (p<0.005). When comparing data on respiratory pressures (manovacuometry and expected) with lifestyle and clinical characteristics, it was noted that the only index that showed statistical relevance was the crossing of the variable breast reconstruction with MaxEP test value (p=0.014). The results of the correlation made between the variables of maximum respiratory pressures with the age of the participants revealed that there is statistical significance between the variables, with the following findings being noted: test MaxIP (p=0.009), expected MaxIP (p=0.008), test MaxEP (p<0.001), expected MaxEP (p<0.001). Considerations: The study showed that there was a reduction in respiratory muscle strength in women who underwent mastectomy, even though there was no statistical significance in crossing manovacuometry measurement data with clinical and surgery-related data.